Innate immunity and early liver inflammation - Yang Zhou, Jordi (Frontiers in Immunology, 2023)
The innate system constitutes a first-line defence mechanism against pathogens. 80% of the blood supply entering the human liver arrives from the splanchnic circulation through the portal vein, so it is constantly exposed to immunologically active substances and pathogens from the gastrointestinal tract. Rapid neutralization of pathogens and toxins is an essential function of the liver, but so too is avoidance of harmful and unnecessary immune reactions. This delicate balance of reactivity and tolerance is orchestrated by a diverse repertoire of hepatic immune cells. In particular, the human liver is enriched in many innate immune cell subsets, including Kupffer cells (KCs), innate lymphoid cells (ILCs) like Natural Killer (NK) cells and ILC-like unconventional T cells – namely Natural Killer T cells (NKT), γδ T cells and Mucosal-associated Invariant T cells (MAIT). These cells reside in the liver in a memory-effector state, so they respond quickly to trigger appropriate responses. The contribution of aberrant innate immunity to inflammatory liver diseases is now being better understood. In particular, we are beginning to understand how specific innate immune subsets trigger chronic liver inflammation, which ultimately results in hepatic fibrosis. In this review, we consider the roles of specific innate immune cell subsets in early inflammation in human liver disease.